ULAMA HIJAZ-JAWA PERTENGAHAN ABAD XIX M; SYEIKH NAWAWI AL-BANTANI DAN PENDIDIKAN TASAWUF - Mukaffa, Zumrotul (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2017)
This article describes a 'hijaz' ulama from Java, Sheikh Nawawi al-Bantani. He is known as the 'fiqh' ulama. However, it turns out he also has a tendency in the field of Sufism. His thoughts on Sufism are so much embodied in his various works. The Sufism here refers to all that is done to keep the heart clear, to cure broken hearts, to adorn the heart with a laudable behaviour and all things that can lead one to a high degree in faith and Islam. According to him, human formation can be done with deepening of the science of Sufism through education. Three of his works in the field of Sufism, Salalim al-Fudhola 'Syarh Mandzumah Hidayah al-Azkiya', Qami 'al-Tughyan Syarh' ala Manzhumah Syu'ab al-Iman, and Nashaih al-'Ibad fi Bayan Alfadz Munabbihat 'ala al-Isti 'dad li Yaum al-Ma'ad, asserted his thoughts that describe a necessity for a Muslim to integrate Shari'a, tariqat and hakikat. Shari'a means to keep all the commandments of God and stay away from His prohibitions; Thariqah deepens into the Shari'a through the activities of sunnah, good deeds, dhikr, riyadlah, and all outwardly and inwardly activities that can lead a person to the essence of himself and his God. The process of integration can be realized through the planting of seven basic characters, the habituation of eleven attitudes of sufism, and exemplary attitudes and behaviors designed in an educational curriculum. Keywords: Ulama 'Hijaz, Shaykh Nawawi al-Bantani, Educational Sufism